THE ANALYZE BUDGET POLICIES IN THE CONTEXT OF THE EFFICIENCY AND EFFECTIVENESS OF ACADEMIC FINANCE AT INTERNATIONAL BALI TOURISM INSTITUTE - Ni Made Widiastuti (Universitas Pendidikan Nasional, 2014)
Budget is an important role in the company management, because budget as aplanning instrument which gave clear direction to achieve the goals and objectives of thecompany beside as aninstrument to improve communication and coordinated the job to docooperation between department also as a tool control to compare the realization withplanning and made improvements if necessary needed.The main objectives of this study were to identify and analyze budget policies in thecontext of the efficiency and effectiveness of academic finance at International Bali TourismInstitute. The obtain data of the study were collected through observation method those wereovert and covert observation, documentation and interviews with the Head of PublicAdministration, Head of Human Resources and Administration, the Head of Student andAlumni, Head of Academic Administration and other participants that were play important rolein the implementation of academic activities in the application framework of Tri DharmaUniversity at International Bali Tourism Institute.The results of the study showed that based on the discussions that have been described,can be concludeseveral conclusions as follows: budgetary policy at The International BaliTourism Institute used the bottom-up approach. It can be seen from The Puket (Vice Chairman)and Division Manager at SPB ATC, MTC SPB, SPB SPA, Head of LPM, Head of Litabmas, asmanager who were responsible for accountability centers, they were applied what they wantto achieve and the kind of resources they necessary need to achieve the goals, the employeeswere involved in budgeting arrangement to achieve the goal in the future. The income for theoperational cost especially academic budgeting came mostly from students payment, the rangefrom 99.11% to 99.71%. The Financial of Academic activities such as providing education,research and community service during the period of the year 2008/2009 to 2012/2013 theobtained efficiency were Rp. 8.127.365 for each student every year. In the learning process theobtained effectiv but to generate students output who were graduated in 2008/2009 to2012/2013 reflects the less effectiveness of learning because there were differences betweenthe students were received in that period with the students who graduated were 13,52% or 475students. The teachers or lecturers have doubles job as an officer and also managing thestructural foundations that condition resulted high workload capacity so the function of thelecturers as researchers and produce less effective scientific research, it can be seen from thebudget funds of period 2012/2013 the total amount Rp.129.900.00 absorbed only Rp. 33.839million (until June 2013). Devotion society during the years 2010 until 2013 was very effective,because the realization of activities and the funds budgeted support were managed withmaximum.Keywords: budget policy, efficiency, effectiveness, academic financial